THE QUANTITY OF AMMONIUM CREATING BACTERIUM OF LIGHT BROWN AND GRAY SEMI DESERT SOILS OF APPLE ORCHARDS AFTER THE INTRODUCTION OF ENTOMO PATHOGEN BACTERIUM CREATING CRYSTALS (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
It has been approved according to the experimental research results, that after insecticide BT(NAR)-3, BT(NAR)-7, BTB, Lepidocide bacterial insecticides do not have negative influence on the qualitative and quantitative composition of bacterium (spurious and non-spurious) ammonium creating of light brown and gray semi desert of apple orchards, which provides the opportunity of broad application of insecticides against the above mentioned phyto fagan.
Keywords: insecticide; light brown and gray semi desert of apple; negative influence; qualitative and quantitative composition